Application of the novel tracer mitoxantrone hydrochloride in lymph node visualization during lateral neck dissection for thyroid carcinoma - Li, Wu; Li, Hui; Tang, Yulong; Wu, Peng; Zhou, Shiwei; Song, Xiaohua; Liu, Zeyang; Wang, Zhiyuan; Shi, Feng; Xia, Xibin; Ai, Zhaodong; Peng, Xiaowei (Frontiers in Endocrinology, 2025)
BackgroundIn this study, a novel lymph node tracer—mitoxantrone hydrochloride injection for tracing (MHI)—was intraoperatively administered into suspected metastatic lateral cervical lymph nodes of patients with papillary thyroid carcinoma (PTC), aiming to evaluate its staining efficacy and clinical value in enhancing the completeness of lateral neck dissection (LND).MethodsA prospective controlled study was conducted at Hunan Cancer Hospital between December 2023 and May 2024, enrolling a total of 67 patients diagnosed with thyroid carcinoma. After informed consent, patients were allocated to either MHI or methylene blue group. Subjects were divided into an MHI group (n = 42) and a methylene blue group (n = 25). All patients underwent LND.ResultsThe results demonstrated no statistically significant differences between the two groups in terms of operative time, total number of lymph nodes dissected, cervical drainage volume, or postoperative length of hospital stay (P > 0.05). However, the MHI group exhibited superior staining of suspected metastatic lymph nodes, with a greater number of metastatic lymph nodes and a higher positive ratio compared to the methylene blue group (P < 0.05).ConclusionMHI causes minimal tissue contamination and can effectively enhance the thoroughness of LND in patients with thyroid carcinoma, demonstrating high clinical application value.